Truth telling and terminal illness: A Jewish view - Schindler, Ruben (Journal of religion and health, 1982)
The focus of this paper is a Jewish view of truth telling and the dilemma of revealing to a terminal patient his imminent demise. Directions are given to physicians, medical personnel, and children of the patient on how to deal with truth telling. Attitudes reflected in Jewish thought suggest that the welfare of the patient is primary, and any information that will upset his psychological state is clearly prohibited. Physicians may not reveal to patients their terminal state. Children and family are obligated to withhold information of a patient's terminal state, even if the latter demands to be told. Hope is seen as a central feature of truth telling even during the period of confession. This view contrasts with the liberal attitude of truth telling in some Western countries, where it is the patient's right to know of his imminent demise.